When Markets Are Social Institutions: Moral Economy and Symbolic Capital in the Buffalo Trade at Bolu Market, Toraja ? - Isak Pasulu; Elisabet Pali (Yayasan Vifada Cendikia Indonesia, 2025)
Purpose: This study examines the process of purchasing decisions and buffalo price determination in the Bolu Animal Market, Toraja Utara, through the perspective of Economic Sociology Research Design and Methodology: The research aims to analyze how economic practices in the traditional livestock market are embedded within social relations, cultural values, and local power structures. This study employed a qualitative approach with a case study design. Data were collected through participant observation, in-depth interviews with traders, buyers, and traditional leaders, as well as supporting documentation. The data were analyzed thematically using the concepts of social embeddedness proposed by Mark Granovetter, moral economy by Karl Polanyi, and social and symbolic capital by Pierre Bourdieu. Findings and Discussion: The findings reveal that purchasing decisions and buffalo price formation are not solely determined by economic rationality or market mechanisms. Instead, these processes are strongly influenced by symbolic values, family prestige, social legitimacy, and customary obligations within Torajan culture. Buffalo characteristics, such as physical appearance, gender, and symbolic markings, interact with social status and actor networks in shaping market transactions. These findings imply that traditional markets should be understood as socio-cultural institutions embedded in local social structures. Implications: The study also highlights the importance of economic sociology perspectives in explaining the dynamics of traditional markets and recommends further research on the transformation of indigenous markets in the context of modernization and commercialization.